2021
DOI: 10.1186/s12888-021-03166-6
|View full text |Cite|
|
Sign up to set email alerts
|

Factors related to age at depression onset: the role of SLC6A4 methylation, sex, exposure to stressful life events and personality in a sample of inpatients suffering from major depression

Abstract: Background An early onset of depression is associated with higher chronicity and disability, more stressful life events (SLEs), higher negative emotionality as described by the primary emotion SADNESS and more severe depressive symptomatology compared to depression onset later in life. Additionally, methylation of the serotonin transporter gene (SLC6A4) is associated with SLEs and depressive symptoms. Methods We investigated the relation of SLEs, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 98 publications
(133 reference statements)
4
7
0
Order By: Relevance
“…The model used to predict depression in this study was able to explain 52% of the variance in depressive symptoms [ 35 ]. Findings of a positive association between the primary emotion SADNESS and SLEs are also in line with the assumption of events associated with at least a symbolical loss triggering the SADNESS system in individuals suffering from depression [ 36 ]. This notion is further supported by a model including SLEs, SEEKING and SADNESS predicting a substantial amount of variance in depression onset [ 36 ].…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…The model used to predict depression in this study was able to explain 52% of the variance in depressive symptoms [ 35 ]. Findings of a positive association between the primary emotion SADNESS and SLEs are also in line with the assumption of events associated with at least a symbolical loss triggering the SADNESS system in individuals suffering from depression [ 36 ]. This notion is further supported by a model including SLEs, SEEKING and SADNESS predicting a substantial amount of variance in depression onset [ 36 ].…”
Section: Introductionsupporting
confidence: 73%
“…Findings of a positive association between the primary emotion SADNESS and SLEs are also in line with the assumption of events associated with at least a symbolical loss triggering the SADNESS system in individuals suffering from depression [ 36 ]. This notion is further supported by a model including SLEs, SEEKING and SADNESS predicting a substantial amount of variance in depression onset [ 36 ]. Accordingly, SEEKING and SADNESS but also the primary emotion FEAR are obvious candidates for the prediction of fear of COVID-19 [ 32 ].…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Interestingly, while there was a (non-significant) positive association between SADNESS and fear of COVID-19 in the healthy controls, SADNESS was negatively associated with fear of COVID-19 in the former inpatients [86]. Sanwald et al [87] also confirmed the increased activity of the SADNESS system with decreased activity of the SEEKING system among young women suffering from depressive disorders compared to male subjects. Montag et al [88] also observed strong associations between higher FEAR and SADNESS scores and depressive tendencies in healthy subjects and depressed individuals.…”
Section: Neural Emotional Systems and Early Maladaptive Schemas In De...mentioning
confidence: 92%